The case of "Nature-Deficit Disorder" (NDD) and its complications in the absence of a Universally Reliable and Valid Self-Reported Tool - Pilafas, Georgios; Chanioti, Maria; Louka, Penelope (Health & Research Journal, 2024)
The present letter to the editors presents the debate over the condition of ‘Nature-Deficit Disorder’ (NDD) and it aims to communicate to the scientific community the need for the creation of valid and reliable tools that would serve in future studies as measures of the condition.